Сто великих загадок истории - Кубеев Михаил Николаевич (Иллюстрированная коллекция, 2008)
Экземпляры: (20101124) / Инвентарный номер: 46247 / Цена: 450.01 / Сис.шифр: 63.3 / Авт.знак: К 88 / ББК: 63.3